Joss Whedon : Conversations - Burkhead, Cynthia; Lavery, David, 1949- (Book collections on Project MUSE., 2011)
No recent television creator has generated more critical, scholarly, and popular discussion or acquired as devoted a cult following as Joss Whedon (b. 1964). No fewer than thirty books concerned with his work have now been published (a forthcoming volume even offers a book-length bibliography), and ten international conferences on his work have convened in the U.K., the United States, Australia, and Turkey. Fitting then that this first volume in the University Press of Mississippi's "Television Conversations" series is devoted to the writer, director, and showrunner who has delivered